Vaskularisasi Pembuluh Darah Arteri Mata (Organum visus) pada Kambing Lokal (Capra sp.) - Idawati Nasution; Ezy Yulanda Rezki; Hamny Hamny (Agricultural Faculty, 2013)
Eye (organum visus) vascular of local goat (capra sp.)ABSTRACT. The aim of the study was to determine of eye vascular in local goat (Capra sp.) The study used a local goat, aged 2 years old. Observation was made after specimen preparation. The observations was documented using a digital camera and analyzed descriptively. The vascular to the eye originated from externa ophthalmica artery and divides into several branched musculares arteries, lacrimalis artery, rete mirabile ophthalmicum gives off supraorbitalis artery, ethmoidalis artery, anteriores ciliares arteries and anastomoses with interna ophthalmica artery and devides into lateralis posterior longae ciliares arteries and medialis posterior longae ciliares arteries and the terminal branched into lateralis posterior shortae ciliares arteries and medialis posterior shortae ciliares arteries. Superficial temporalis artery gives off two branches lateralis inferior palpebral artery and lateralis superior palpebral artery. Malaris artery gives off two branched medial inferior palpebral artery and medial superior palpebral artery.